Avoiding lodging in irrigated spring wheat. II. Genetic variation of stem and root structural properties - Piñera-Chavez, F.J.; Berry, P.M.; Foulkes, M.J.; Molero, G.; Reynolds, M.P. (Elsevier, 2016)
Lodging-related traits were evaluated on the CIMMYT Core spring wheat Germplasm Panel (CIMCOG) in the Yaqui Valley of North-West Mexico during three seasons (2010–2013). Genetic variation was significant for all the lodging-related traits in the cross-year analysis, however, significant G × E interaction due to rank changes or changes in the absolute differences between cultivars were identified. The inconsistences on cultivar performances across seasons particularly reduced the heritability of key characters related to root lodging resistance (anchorage strength). Target characters related to stem lodging resistance (stem strength) showed good heritability values equal or above 0.70. Positive correlations between stem strength and stem diameter and between root plate spread and root strength were found. Selecting for greater stem diameter and wall width, greater root plate spread and shorter plant height could enable breeders to increase lodging resistance by increasing stem strength, root strength and decreasing plant leverage, respectively. Achieving a lodging-proof crop will depend on finding a wider root plate spread and implementing new management strategies. Genetic linkages between lodging traits will not constrain the combination of the key lodging-trait dimensions to achieve a lodging-proof ideotype. However, strong association between stem strength and stem wall width will increase the total biomass cost needed for lodging resistance.